The impact of the COVID-19 pandemic on the perinatal mental health of women - Tom Farrell (7951295) (2020)
Objectives The physical health impact of the coronavirus disease infection (COVID-19) has received attention worldwide; however, data around the psychological impact of the pandemic is still emerging and little has been reported on psychological effects among vulnerable groups. This study was undertaken with the aim of studying the impact of the COVID-19 pandemic and related restrictions on perinatal mental health among women in Qatar. Methods A cross- sectional survey of women accessing maternity services in Qatar was carried out during the months of June and July 2020 at the local peak of the pandemic. Background data including relevant demographic details, pregnancy and mental health history, concerns, as well as helpful stress-reducing factors reported by women was collected. Depression and anxiety symptomatology was studied using the Patient Health Questionnaire Anxiety-Depression Scale (PHQ-ADS). Results The survey results revealed a high prevalence of anxiety and Depressive symptomatology (34.4 and 39.2% respectively), based on PHQ-ADS scoring. These rates appeared much higher than the reported pre-pandemic prevalence and were not affected by occupation, previous mental health problems or pregnancy complications. Women’s most commonly reported concerns as well as coping factors are discussed. Conclusions Results indicate a marked increase in anxiety and depressive symptoms during the COVID-19 pandemic, among pregnant and puerperal individuals, who constitute a vulnerable group with respect to mental health morbidity. These findings can be used to inform public health interventions, among which, consideration should be given to routine mental health screening of vulnerable groups during major health crises. Other information  Published in: Journal of Perinatal Medicine License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/jpm-2020-0415